Association of blood urea nitrogen to creatinine ratio and long-term outcome among women with coronary artery bypass grafting surgery: filling gaps in female - Kai Zhang; Rong Zhang; Bo Li; Dan Cui (BMC Nephrology)
Abstract Background The blood urea nitrogen to creatinine ratio (BUN/Cr) has been associated with poorer outcomes in various cardiovascular diseases, including acute and chronic heart failure (HF). However, its significance in female patients undergoing coronary artery bypass grafting (CABG) remains largely unexplored. Methods We utilized data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. The primary outcome was long-term mortality at one, two, three, four, and five years post-surgery. The relationship between BUN/Cr and the risk of long-term mortality in patients with CABG was evaluated using Cox proportional hazards and restricted cubic spline models. Subgroup analyses were conducted to investigate the prognostic value of BUN/Cr across different patient subgroups. Results The study included 1,358 participants with a mean age of 70.9 years (range: 60.9–80.8) and a mean body mass index (BMI) of 30.8 kg/m² (range: 24–37.6). A one unit increase in BUN/Cr was associated with lower one-year mortality after adjusting for all covariates (hazard ratio (HR) 0.95, 95% CI 0.91–0.98). Participants in the lowest BUN/Cr category (Q1, ≤ 15) exhibited a significantly higher risk of mortality (HR: 2.67, 95% CI: 1.36–5.27, p = 0.004) compared to the reference group (Q4). Restricted cubic spline analysis revealed an L-shaped relationship between BUN/Cr levels and long-term mortality, with an inflection point at 17.308. Stratified and sensitivity analyses further supported these findings. Conclusions These results suggest an L-shaped association between BUN/Cr and long-term mortality among female patients undergoing CABG, which will provide a unique perspective for clinical management of the special group of women undergoing CABG.